Finite-Time Stability of Solutions for Nonlinear q-Fractional Difference Coupled Delay Systems - Jingfeng Wang; Chuanzhi Bai (Discrete Dynamics in Nature and Society)
In this paper, we investigate and prove a new discrete q-fractional version of the coupled Gronwall inequality. By applying this result, the finite-time stability criteria of solutions for a class of nonlinear q-fractional difference coupled delay systems are obtained. As an application, an example is provided to demonstrate the effectiveness of our result.